Assessing the impact of various tuberculin PPD brands on bovine tuberculosis diagnosis - Echeverria, Gustavo; Zumarraga, Martin Jose; Proaño‑Pérez, Freddy; Barceló Blasco, Francisco; Waard, Jacobus H. de (Springer Nature, 2024)
Although several brands of tuberculin purified protein derivatives (PPDs) are available for diagnosing bovine tuberculosis (bTB), comparative studies to determine their diagnostic accuracy are infrequent. In Ecuador we compared two different PPD brands for bTB diagnosis using skin testing and measuring skin thickness increase. Additionally, we evaluated four PPD brands, including those used for skin testing, in the Bovine Tuberculosis Interferon Gamma Test (IFN-γ test) measuring IFN-γ induction in whole blood. The study included 17 naturally tuberculosis-infected PPD and IFN-γ test positive bovines. Both the field and laboratory results showed significant differences in classifying the 17 bovines as bTB positive or negative. We hypothesize that several factors, such as the genetic background of the cows, sensitization to environmental mycobacteria, M. bovis strains involved in the bTB infection, and the manufacturing procedures of the PPDs, could have influenced the immune reaction toward the different tuberculin PPD brands. Our study emphasizes the necessity for comparative studies aimed at determining the diagnostic accuracy of PPD brands for bTB diagnosis as well as the development of standardized methods for PPD production and potency determination.